2012
DOI: 10.1016/j.febslet.2011.12.038
|View full text |Cite
|
Sign up to set email alerts
|

SNPs of hemocyanin C‐terminal fragment in shrimp Litopenaeus vannamei

Abstract: a b s t r a c tIn this study, we identified a variable region in the C-terminus of hemocyanin from the shrimp Litopenaeus vannamei (2288-2503 bp, HcSC) by sequence alignments. A total of 13 SNPs were identified by PCR-SSCP and HcSC clone sequencing. The SSCP patterns of HcSC could be modulated in Vibro parahaemolyticus-treated shrimps. A novel SSCP band with four SNP sites was identified in V. parahaemolyticus-resistant shrimps. More importantly, three of these four SNPs introduced variations in amino acid seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Previous studies have shown that hemocyanin exerted its antimicrobial function based on different mechanisms including glycosylation modification (Zhang et al 2017) and molecular polymorphism (Zhao et al 2016; Lu et al 2015; Guo et al 2013; Zhao et al 2012, 2013). Here, we predicted and characterized a novel hemocyanin-derived antimicrobial peptide L1 using bioinformatics, followed by experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hemocyanin exerted its antimicrobial function based on different mechanisms including glycosylation modification (Zhang et al 2017) and molecular polymorphism (Zhao et al 2016; Lu et al 2015; Guo et al 2013; Zhao et al 2012, 2013). Here, we predicted and characterized a novel hemocyanin-derived antimicrobial peptide L1 using bioinformatics, followed by experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [38] found that the main protein directly bound to the Vibrio alginolyticus , Vibrio harveyi , A. hydrophila , and Staphylococcus aureus in L. vannamei serum was hemocyanin, suggesting that hemocyanin possesses antibacterial functions. The C-terminus of L. vannamei hemocyanin is possibly related to the immunity in shrimp to different pathogens [39]. Gram-negative bacteria A. hydrophila are a common species of the Aeromonas genus in water and water habitants [40].…”
Section: Discussionmentioning
confidence: 99%
“…These amino acid substitutions likely confer alternate functionality to newly synthesised Hbs. Similarly, 13 Hc-associated SNPs have been identified in shrimp ( L. vannamei ) infected with the same pathogens [142, 143]. These molecular alterations were located in the immunoglobulin-like domain and C-terminal region of the shrimp Hc resulting in improved microbial agglutination properties.…”
Section: An Emerging Role For Invertebrate (Bivalve) Hemoglobin In Inmentioning
confidence: 99%